Successful pregnancy in asevere hypertensive patient treated with nitrendipine. Case report - Colina Chourio, José; Godoy, Nereyda; Oliveros Palacios, María; Nery Villarroel, María; Arocha, Ildefonzo (Investigación Clínica, 2013)
Nitrendipine (NIT), a new potent calcium channel blocking agent, was administered to a patient with essential severe (191 /119 mm Hg), refractory, and resistant hypertension (HT) to conventional triple drug regime. Three previous pregnanc1es had been unsuccessful the past 4 years because of uncontrollable HT and repeated hypertensive crisisses. NIT (20 mg tablets) was given PO as a single morning dose and 15 months after BP control, she became pregnant again. With a 20 mg/day dose of NIT throughout pregnancy, a healthy 2400 g. 47 cm male boy was delivered by a non-emergency cesarean section at37 weeks’ pregnancy. Both mother and son rema1n normal months after birtb. The results suggest NIT may be considered as an alternative for this type of patients and should be studied in clinical trials.